Vanadium pentoxide-based cathode materials for lithium-ion batteries : morphology control, carbon hybridization, and cation doping - Huang, Xin (2015)
Vanadium pentoxide (V2O5) is a promising cathode material for high-performance lithium-ion batteries (LIBs) because of its high specific capacity, low cost, and abundant source. However, the practical application of V2O5 in commercial LIBs is still hindered by its intrinsic low ionic diffusion coefficient and moderate electrical conductivity. In the past decades, progressive accomplishments have been achieved that rely on the synthesis of nanostructured materials, carbon hybridization, and cation doping. Generally, fabrication of nanostructured electrode materials can effectively decrease the ion and electron transport distances while carbon hybridization and cation doping are able to significantly increase the electrical conductivity and diffusion coefficient of Li+. Implementation of these strategies addresses the problems that are related to the ionic and electronic conductivity of V2O5. Accordingly, the electrochemical performances of V2O5-based cathodes are significantly improved in terms of discharge capacity, cycling stability, and rate capability. In this review, the recent advances in the synthesis of V2O5-based cathode materials are highlighted that focus on the fabrication of nanostructured materials, carbon hybridization, and cation doping.